Optical and molecular diversity of dissolved organic matter in sediments of the Daning and Shennong tributaries of the Three Gorges Reservoir - Wang, Kai; Fang, Hongwei; He, Guojian; Huang, Lei; Cui, Zhenghui; Gao, Qifeng; Xu, Song; Wang, Dianchang; Wu, Xinghua; He, Ding (Frontiers in Environmental Science, 2023)
Introduction: Damming significantly modifies the function of natural river networks and influences sediment dynamics with a reservoir’s operation. The dissolved organic matter (DOM) in reservoir sediments severely affects carbon flow from land to sea. However, the properties of DOM (e.g., quantity and quality) in reservoir sediments and their relationship with carbon cycling remain unclear as complex reservoir construction interrupts the environmental processes. Methods: This study characterizes the optical and molecular properties of sediment water-extractable organic matter (WEOM) in the Daning and Shennong tributaries of the world’s largest reservoir—the Three Gorges Reservoir (TGR)—by applying optical techniques and ultrahigh-resolution Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). Results and Discussion: We first assessed the link between light-absorbing components and the individual molecules in WEOM, which were significantly different than DOM in water and indicated that there might be an intrinsic variation between DOM in sediment and in water. Then, with the unique optical–molecular property linkage assessed, multiple sources (autochthonous and terrestrial) were identified, and a declining trend of terrestrial and recalcitrant WEOM was revealed from the tributaries upstream to downstream. Finally, through covariance analysis of the properties between WEOM and sediment particles, we demonstrated that the WEOM dynamic was most likely regulated by hydrologic sorting-induced particle size and mineral composition variations of sediment. Moreover, assessment between lability and WEOM molecular properties suggested that the WEOM dynamic likely contributes to carbon burial in the reservoir. This study emphasizes the influence of dam construction on organic matter accumulation and riverine carbon cycling.